2014
DOI: 10.1007/s00253-014-5721-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of autophagy and its significance in cellular homeostasis

Abstract: Autophagy is a catabolic pathway that regulates homeostasis in cells. It is an exceptional pathway of membrane trafficking. Autophagy is characterized by the formation of double-membrane vesicles; autophagosomes that are responsible for delivering damaged organelle and extra proteins to lysosome for recycling. A series of actions including environmental and genetic factors are responsible for induction of autophagy. In the past few decades, the research on autophagy has been immensely expanded because it is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 107 publications
0
33
0
Order By: Relevance
“…The protein products of Atgs are organized in five functional groups, namely: (i) the Unc-51-like kinase (Ulk):Atg13:FIP200 initiation complex (Ganley et al, 2009; Hosokawa et al, 2009); (ii) the beclin1:hVps34[phosphatidylinositol 3 (PI3) kinase]:Atg14L nucleation complex (Itakura et al, 2008); (iii) the PI3–phosphate-binding WIPI-1/2 complex (Proikas-Cezanne et al, 2004; Vergne et al, 2009); (iv) the Atg5–Atg12 conjugation complex activated by Atg7 (Mizushima et al, 1998); and (v) the Atg8 (LC3) conjugation system (Kabeya et al, 2000). These protein complexes participate at specific stages in the autophagic process: initiation, formation, elongation, and fusion (Mehrpour et al, 2010; Awan and Deng, 2014); they are also controlled by several other signaling pathways that fine tune autophagy to regulate the pace of autophagosome formation.…”
Section: Autophagy and Its Role In Skeletal Muscle Homeostasismentioning
confidence: 99%
“…The protein products of Atgs are organized in five functional groups, namely: (i) the Unc-51-like kinase (Ulk):Atg13:FIP200 initiation complex (Ganley et al, 2009; Hosokawa et al, 2009); (ii) the beclin1:hVps34[phosphatidylinositol 3 (PI3) kinase]:Atg14L nucleation complex (Itakura et al, 2008); (iii) the PI3–phosphate-binding WIPI-1/2 complex (Proikas-Cezanne et al, 2004; Vergne et al, 2009); (iv) the Atg5–Atg12 conjugation complex activated by Atg7 (Mizushima et al, 1998); and (v) the Atg8 (LC3) conjugation system (Kabeya et al, 2000). These protein complexes participate at specific stages in the autophagic process: initiation, formation, elongation, and fusion (Mehrpour et al, 2010; Awan and Deng, 2014); they are also controlled by several other signaling pathways that fine tune autophagy to regulate the pace of autophagosome formation.…”
Section: Autophagy and Its Role In Skeletal Muscle Homeostasismentioning
confidence: 99%
“…Autophagy is regarded as a cellular self-digestion process in response to a wide range of deleterious stimuli, through which cytoplasmic materials or organelles integrate into lysosomes for further degradation (47). Previous studies have reported that, autophagy serves a crucial role in the development, differentiation, survival and homeostasis of cells (48)(49)(50)(51). During organ I/R injury, autophagy may help cells respond to injury.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagosome maturity occurs through fusion with the lysosome, which contains lysosomal acid proteases that degrade the engulfed materials( Figure 3; Awan & Deng, 2014;Glick et al, 2010;Jiang et al, 2014;Mizushima, 2007;Mizushima, Yoshimori, & Ohsumi, 2011).…”
Section: Autophagymentioning
confidence: 99%